2017
DOI: 10.1016/j.jvs.2017.03.250
|View full text |Cite
|
Sign up to set email alerts
|

RS06 A Randomized Study Evaluating Negative-Pressure Therapy to Decrease Vascular Groin Wound Complications

Abstract: for future analysis. The majority of short-term readmissions are related to the index procedure; however, long-term readmission rates are related to systemic comorbidities. Targeted patient interventions may improve readmission rates, particularly in those with nonprivate insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…All the included studies reported a reduced incidence of SSIs in the NPWT group compared with the standard dressing group. The results were significant in three studies. Meta‐analysis of the seven studies, including all incisions from all arterial procedures, showed a reduction of SSIs, with an OR of 0·35 (95 per cent c.i.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…All the included studies reported a reduced incidence of SSIs in the NPWT group compared with the standard dressing group. The results were significant in three studies. Meta‐analysis of the seven studies, including all incisions from all arterial procedures, showed a reduction of SSIs, with an OR of 0·35 (95 per cent c.i.…”
Section: Resultsmentioning
confidence: 92%
“…). Of these, seven studies (from 13 records) were considered to have met the inclusion criteria: Kwon et al ,. Gombert et al ,.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations